The epigenetic signatures of opioid addiction and physical dependence are prevented by D-cysteine ethyl ester and betaine - McDonough, Jennifer; Singhal, Naveen K.; Getsy, Paulina M.; Knies, Katherine; Knauss, Zackery T.; Mueller, Devin; Bates, James N.; Damron, Derek S.; Lewis, Stephen J. (Frontiers in Pharmacology, 2024)
We have reported that D,L-thiol esters, including D-cysteine ethyl ester (D-CYSee), are effective at overcoming opioid-induced respiratory depression (OIRD) in rats. Our on-going studies reveal that co-injections of D-CYSee with multi-day morphine injections markedly diminish spontaneous withdrawal that usually occurs after cessation of multiple injections of morphine in rats. Chronically administered opioids are known to alter cellular redox status, thus inducing an oxidative state and an overall decrease in DNA methylation resulting in the transcriptional activation of previously silenced long interspersed elements (LINE-1) retrotransposon genes. The first objective of the present study was to determine whether D-CYSee and the one carbon metabolism with the methyl donor, betaine, would maintain redox control and normal DNA methylation levels in human neuroblastoma cell cultures (SH-SY5Y) under overnight challenge with morphine (100 nM). The second objective was to determine whether D-CYSee and/or betaine could diminish the degree of physical dependence to morphine in male Sprague Dawley rats. Our data showed that overnight treatment with morphine reduced cellular GSH levels, induced mitochondrial damage, decreased global DNA methylation, and increased LINE-1 mRNA expression. These adverse effects by morphine, which diminished the reducing capacity and compromised the maintenance of membrane potential of SH-SY5Y cells, was prevented by concurrent application of D-CYSee (100 µM) or betaine (300 µM). Furthermore, our data demonstrated that co-injections of D-CYSee (250 µmol/kg, IV) and to a lesser extent, betaine (250 µmol/kg, IV), markedly diminished the development of physical dependence induced by multi-day morphine injections (escalating daily doses of 10-30 mg/kg, IV), as assessed by the lesser number of withdrawal phenomena elicited by the injection of the opioid receptor antagonist, naloxone (1.5 mg/kg, IV). These findings provide evidence that D-CYSee and betaine prevent the appearance of redox and epigenetic signatures of opioid physical dependence/addiction in neural cells and lessen development of physical dependence to morphine.